The relationship between public sentiment and the media on the 2022 national elections in the Philippines using granger causality - Chen, Fong-Xiang Gracia (Animo Repository, 2022)
The reliance on local news outlets for information may have a significant influence on people’s opinions and sentiments, especially with a trending topic as the 2022 National Elections. This study aimed to verify this by investigating the existence and direction of that influence. Public tweets regarding this election were collected from the general public and the top 5 local news outlets. These were classified into positive, negative, or neutral via sentiment analysis using VADER. Using the proportion of positive and negative tweets per day for each group, autoregressive (AR) and vector autoregressive (VAR) models were fitted to each time series variable. Presence and direction of a causal relationship between each pair of variables was determined using Granger Causality. This showed that sentiment of news tweets had a Granger causal effect on the sentiment of the general public, thereby highlighting the influence of the news that people consume towards their own sentiments.